The Music Market in the Age of Download - Iacopo Grassi (Fondazione Eni Enrico Mattei (FEEM), 2007)
Internet, mp3 files, peer-to-peer software and digital technologies for copying have radically modified the music sector. In this paper I present a theoretical model, that investigates the consequences of the appearance of a pirate low quality good (typically a mp3 file) in the music market. In this paper I propose a model of sampling, consider the possibility that the firm modifies its business entering into the low quality segment and investigate the supposed conflict between the recording company, whose profit depends on the CD sold, and the artist, whose profits depend in part on the live performance, the demand of which can increase for the positive externality due to the illegal download of music.
Keywords: L86; 330; File-sharing; Copyright; Sample Effect; Mp3; Concert; Musikwirtschaft; Urheberrecht; Bespielte Medien; Produktqualität; Theorie